Effectiveness of the Innovation of the Waste Segregation System (WSS) at the Student Centre at Polytechnic Melaka - Rahim, Munirah Abdul; Adnan, Suzana Wati Binti (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Waste segregation plays a crucial role in supporting sustainability, particularly in busy environments like educational institutions, where waste is generated daily. This study aims to evaluate the effectiveness of the Waste Segregation System (WSS) developed for the Student Centre at Polytechnic Melaka. Background Problems: The need for efficient waste segregation in high-traffic areas, such as student centers, is critical. Common mistakes in waste separation often occur with traditional recycling bins, leading to contamination of recyclable materials. Research Methods: The WSS allows users to select the correct waste category by pressing a button, triggering an automatic rotation of the bin to the proper compartment. The system’s performance was evaluated based on ease of use, improvement in segregation accuracy, and student response. Finding/Results: Initial observations indicate that students are more likely to separate waste properly when using the system. This leads to reduced contamination between wet and dry waste, making recyclable materials cleaner and easier to process. Conclusion: The WSS proves to be a practical and effective solution for improving recycling habits. It has the potential for wider adoption in institutions and public spaces aiming to enhance waste management and sustainability.